EXAMINING THE EFFECTS OF CHATGPT-ASSISTED PRACTICE ON VOCABULARY ACQUISITION AMONG EMI UNIVERSITY STUDENTS (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2026)
The use of artificial intelligence tools in vocabulary learning has gained significant attention recently, with ChatGPT emerging as a potentially game-changing resource for language education. Despite the growing interest, there is limited empirical evidence on the effectiveness of ChatGPT-assisted vocabulary practice in English as a Medium of Instruction (EMI) settings. This study investigates the impact of ChatGPT-assisted vocabulary practice on EMI students' vocabulary development. Over four weeks, a quasi-experimental design compared this new method with traditional vocabulary learning strategies. Sixty EMI students from History, Philosophy, and Pedagogy programs at Fergana State University took part in the research. Pre- and post-vocabulary tests assessed lexical acquisition. Significant improvement is anticipated in the group using ChatGPT-assisted practice compared to the control group. The findings aim to enhance EMI pedagogy and provide insights into effective AI use in academic vocabulary teaching.